A synthesis of the evidence regarding safety of a Chinese herbal formula Shufeng Jiedu: A pharmacological review - Jeanne Trill; Zhijie Wang; Merlin Willcox; Yu Zhang; Xiao-Yang Hu; Michael Moore (Pharmacological Research - Modern Chinese Medicine, 2022)
Shufeng Jiedu capsule (SFJDC) is a Chinese herbal medicine formula for treating acute respiratory tract infections. This review aims to assess its potential safety for clinical setting.Systematic literature searches were conducted across multiple databases to: investigate the phytochemistry and safety data on SFJD and its constituents; and to produce a meta-analysis of RCTs reporting safety concerns (all ages) receiving SFJDC capsule (any condition). The primary outcome was the incidence of adverse events (AEs) or complications associated with taking SFJDC with/without usual care compared with placebo or usual care.Pharmacovigilance data reporting AEs to the Chinese National Adverse Drug Reaction Monitoring System in 2017/2018 was analysed.Safety information was insufficient regarding pregnancy/lactation (all herbs). Laboratory studies raised theoretical concerns regarding saikosaponins A and D elevating blood glucose; glycyrrhizin inducing hypertension and hypokalaemia; and saikosaponins/resveratrol/lignans reducing platelet activity. However, these occurred at much higher doses than used clinically.Sixty-four RCTs (7612 participants) met the meta-analysis criteria. Fourteen additional trials and two case studies were also considered. Minor AEs included nausea/vomiting, diarrhoea, unspecified gastrointestinal discomfort, dizziness and rash; these were not significantly different (statistically) to control groups.Across 2017 and 2018 sales of SFJDC packs (content 36 capsules) totalled 23.2 million. AEs recorded were 169 (2017) and 198 (2018). The majority were gastrointestinal, and improved on stopping SFJDC. None included the potential phytochemical concerns (regarding platelets, hypertension, hypokalaemia, blood glucose).No serious AEs were identified from the included trials or pharmacovigilance data.No substantive safety concerns were identified for SFJD for clinical use; excluding pregnant/lactating women.